A Simultaneous Study of the Size, Earnings/Price, and January Effects in the Stock Markets of Taiwan, Korea, and Thailand - DING, David K. (Institutional Knowledge at Singapore Management University, 1996)
This study examines the size, earnings/price, January, and interaction effects in the stock markets of Taiwan, Korea, and Thailand. Various portfolio formation methods, namely, the Within Groups, Independent Groups, and Within Groups with Randomization methods are employed together with three different definitions of excess returns--Comparison, Market-Adjusted, and Market Model returns. We find the presence of a strong January effect, especially for Taiwan and Korea. The tax-loss selling hypothesis cannot be used to explain this effect. Rather, employees' investment of their year-end bonus income may contribute to such an effect. Size and earnings/price effects are much less pronounced in these countries than in the United States. Moreover, interaction effects do not seem to explain the portfolio returns.